2012
DOI: 10.1093/scan/nss068
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous attention to facialvsnon-facial emotional visual stimuli

Abstract: The capacity of the two types of non-symbolic emotional stimuli most widely used in research on affective processes, faces and (non-facial) emotional scenes, to capture exogenous attention, was compared. Negative, positive and neutral faces and affective scenes were presented as distracters to 34 participants while they carried out a demanding digit categorization task. Behavioral (reaction times and number of errors) and electrophysiological (event-related potentials-ERPs) indices of exogenous attention were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 83 publications
8
46
1
Order By: Relevance
“…Interestingly, P2 amplitudes were affected by uncertainty only, which contrasts with previously reported modulations by highly arousing stimuli (Carretié et al, 2004;Carretié et al, 2013;Foti & Hajcak, 2008). Apparently, the uncertainty-induced increase in early attentional capture cannot be further modulated by selective processing of neutral and aversive stimuli.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Interestingly, P2 amplitudes were affected by uncertainty only, which contrasts with previously reported modulations by highly arousing stimuli (Carretié et al, 2004;Carretié et al, 2013;Foti & Hajcak, 2008). Apparently, the uncertainty-induced increase in early attentional capture cannot be further modulated by selective processing of neutral and aversive stimuli.…”
Section: Discussioncontrasting
confidence: 97%
“…As an indicator of early selective attention, it has been shown to index feature detection processes in nonaffective stimuli (Luck & Hillyard, 1994), but also to be enhanced for emotionally relevant pictures (Carretié, Hinojosa, Martín-Loeches, Mercado, & Tapia, 2004;Carretié et al, 2013;Foti & Hajcak, 2008). The late positive potential (LPP) is a centro-parietal slow wave beginning in the P3 time window, around 300 ms after stimulus presentation, that is more positive for motivationally salient stimuli such as targets or emotional pictures Schupp et al, 2000).…”
mentioning
confidence: 99%
“…were prominent both in the present and in previous studies (Hopfinger & Mangun, 2001, Carretié et al 2013bLuck 2012 Figure 2 about here ***…”
Section: Resultssupporting
confidence: 83%
“…Enhanced amplitudes of P1p (or posterior P1) in response to spiders presented as distractors in tasks similar to that employed here (concurrent but distinct target-distractor tasks, or CDTD) have previously been reported (Carretié et al 2005;Carretié et al 2009). Additionally, sensitivity of P2a (or anterior P2) to the emotional content of distractors has been frequently reported too, with greater amplitudes for negative distractors, as compared to neutral, being consistently found (Carretié et al 2004;2011;2013b;Feng et al 2012;Holmes et al 2006;Junhong et al 2013). Finally, P3o (or occipital P3, since it showed maximal amplitudes in this scalp region) has been also reported in CDTD tasks, such as visual search tasks (Luck 2012), and must be distinguished from the well-known centro-parietal P3 or P3b, and from fronto-central P3, also termed P3a or novelty P3.…”
Section: P3omentioning
confidence: 99%
“…However, to our knowledge, there are not studies addressing the interaction between cognitive performance observed in these training programs and emotional stimuli. For filling this gap here we study two types of stimuli, scenes and faces (Coan & Allen, 2007), because (a) they are important in evolutionary terms (Carretié et al, 2013), and (b) they are known to interact with cognitive requirements (e.g., Eastwood, Smilek, & Merikle, 2003). Furthermore, the most frequently administered visual stimuli in affective neuroscience are based on faces depicting different emotional expressions (e.g., POFA, Ebner, Riediger, & Lindenberger, 2010;KDEF, Lundqvist and Litton, 1998) or scenes showing positive, neutral and negative displays (e.g., IAPS, Lang, Bradley, & Cuthbert 2005).…”
Section: Introductionmentioning
confidence: 99%